An interface optimization and application for the numerical solution of optimal control problems - Heinkenschloss, Matthias (1999)
An interface between the application problem and the nonlinear optimization algorithm is proposed for the numerical solution of distributed optimal control problems. By using this interface, numerical optimization algorithms can be designed to take advantage of inherent problem features like the splitting of the variables into states and controls and the scaling inherited from the functional scalar products. Further, the interface allows the optimization algorithm to make efficient use of user-provided function evaluations and derivative calculations.